A system of marine animal bioconstructions in the mesophotic zone along the Southeastern Italian coast - Cardone, Frine; Corriero, Giuseppe; Longo, Caterina; Pierri, Cataldo; Gimenez, Guadalupe; Gravina, Maria Flavia; Giangrande, Adriana; Lisco, Stefania; Moretti, Massimo; De Giosa, Francesco; Mercurio, Maria; Marzano, Carlotta Nonnis (Frontiers in Marine Science, 2022)
A widespread and diversified mesophotic system of carbonate bioconstructions along the Southern Adriatic and Ionian Italian coasts is described, providing new data on the distribution, structure and associated megabenthic assemblages of mesophotic Mediterranean bioconstructions. The bioconstructions were detected at six different sites off the coasts of Apulia, in presence of marked morphological escarpments, developing on a basal substrate consisting of meso-Cenozoic carbonate rocks. Two biogenic structure types were observed, one mainly built by the nonsymbiotic scleractinians Phyllangia americana mouchezii and Polycyathus muellerae, at depths between approximately 35 and 55 m, and the other by the oyster Neopycnodonte cochlear, at depths from approximately 40 to 70 m. A total of 52 taxa of megabenthic invertebrates, belonging to 6 phyla, were found on the surface of the mesophotic bioconstructions, thus confirming the role of biodiversity hotspots of these carbonate structures. Megabenthic assemblages showed a remarkable heterogeneity both in pattern of species and abundance, probably depending on both the morphological differences of the seabed and the life traits of the single species. Primary bioconstructors seemed to influence the associated community pattern. This peculiar system deserves sound conservation measures in the light of the holistic ecosystem approach for the management of coastal marine areas.